Pentingnya Konsep Diri Dalam Mensikapi Revolusi Jepang - Sri Sudarsih (KIRYOKU, 2019)
Japan is a developed country that still upholds fundamental values which are then used as a basis for attitude and daily behavior. This research aims to examine the self-concept in responding to the Japanese revolution. This research is qualitative in philosophy. The method used is description and interpretation. The right self-concept becomes the main capital to be able to identify various national problems. The concept of self is something important in responding to the revolution of society in Japan. This appears in an open attitude to accept the reality of himself and other nations so that they are willing to learn in total to other more advanced nations. The result is that Japanese society has risen faster in its self-confidence and can catch up, moving ahead of developing more modern western nations. All this happened because all the officials until the people have a national commitment.